SISTEM MATA PENCAHARIAN HIDUP NELAYAN TRADISIONAL SUKUBANGSA KAMORO DI DESA TIPUKA KECAMATAN MAPURUJAYA KABUPATEN MIMIKA PROPINSI PAPUA - Kemong, Bonefasius (Universitas Sam Ratulangi, 2014)
Geographically, the fishing community is the people who live, grow and thrive in coastal areas, which is a transition area between land and sea. As a system, the fishing community consists of social categories that make up the social unity. They also have a system of values and symbols of culture as a reference of their everyday behavior. Like any other community who lived in the coastal and river side area, the Kamoronese, predominantly worked as fishermen. In term to fulfilling’s their livelihood needs, they are not only depends the commodities to the river’s and sea’s species but to the brackish water also. Principal livelihood in the village of Tipuka is as fishermen. Since time immemorial until now generally Kamoro and in particular Tipuka village, their very lives depend on nature. Dependence and their survival is not out of three elements, locally named sagu, sampan dan sungai (3S). Knowledge of culture thus affect the fishing community awareness Kamoro in improving the standard of living better is very less, to sell fisheries aid package provided by the PTFI for various reasons . There were selling outboard motors to entrepreneurs to buy basic needs. Keywords : fisherman, Kamoro, coast